Production activities and economic dependency by age and gender in Europe - Hammer, Bernhard; Prskawetz, Alexia; Freund, Inga (My University, 2015)
We compare selected European countries using an economic dependency ratio which emphasizes the role of age-specific levels of production and consumption. Our analysis reveals large differences in the age- and gender-specific level and type of production activities across selected European countries and identifies possible strategies to adjust age-specific economic behaviour to an ageing population. The cross-country differences in economic dependency of children and elderly persons are largely determined by the age at which people enter, respectively exit, the labour market. The ability of the working age population to support children and elderly persons in turn is strongly influenced by the participation of women in paid work. We also provide a measure for the age-specific production and consumption in form of unpaid household work. The inclusion of unpaid household work leads to a decrease of the gender differences in production activities and indicates that the working age population supports children and elderly persons not only through monetary transfers but also through services produced by unpaid work (e.g. childcare, cooking, cleaning. . .). Given the available data, we cannot distinguish the age profile of consumption by gender and have to assume – in case of unpaid work - that each member of the household consumes the same. Hence, our results have to be regarded as a first approximation only. Our paper aims to argue that a reform of the welfare system needs to take into account not only public transfers but also private transfers, in particular the transfers in form of goods and services produced through unpaid household work.
A cross-country comparison
Keywords: Wirtschaft; Alter; Arbeit; Hausarbeit; Geschlecht; Wohlfahrtsstaat; 330 Wirtschaft